Effect of Tulathromycin on Colonization Resistance, Antimicrobial Resistance, and Virulence of Human Gut Microbiota in Chemostats - Hao, Haihong; Zhou, Shengxi; Cheng, Guyue; Dai, Menghong; Wang, Xu; Liu, Zhenli; Wang, Yulian; Yuan, Zonghui (Frontiers in Microbiology, 2016)
To evaluate microbiological safety of tulathromycin on human intestinal bacteria, tulathromycin (0, 0.1, 1,10 and 100μg/mL) was added into Chemostats. Before and after drug exposure, we monitored 1) population, SCFA products, antimicrobial resistance and colonization resistance of gut microbiota, and 2) the antimicrobial resistance genes, transferability, virulent genes, pathogenicity of Enterococus faecalis. Results showed that low level of tulathromycin did not exhibit microbiological hazard on resistance selection and colonization resistance. However, high level of tulathromycin (10 and 100 µg/mL) may disturb colonization resistance of human gut microbiota and select antimicrobial resistant E. faecalis. Most of the selected resistant E. faecalis carried resistant gene of ermB, transferable element of Tn1545 and three virulence genes (esp, cylA and ace). One of them (E. faecalis 143) was confirmed to have higher horizontal transfer risk and higher pathogenicity. The calculated no observable adverse effect concentration (NOAEC) and microbiological acceptable daily intake (mADI) in our study was 1μg/mL and 14.66µg/kg.bw/day, respectively.